Efektifitas Penggunaan Buku “Diari Gigi Sehat” terhadap Perilaku Orang Tua dalam Menjaga Kebersihan Gigi dan Mulut Anak Di Pontianak - Yeni Maryani; Pawarti Pawarti; Asmaul Husna; M Ibraar Ayatullah (Jurnal Sehat Mandiri, 2022)
Mother is an important factor in maintaining the cleanliness of the child's teeth and mouth. For this reason, mothers need media to increase their knowledge. This study aims to determine changes in the behavior of mothers in maintaining the health of their children's teeth and mouth by using the book "Healthy Dental Diary". This research is a Quasi-Experimental without a Control group with One Group Pre and Posttest Design. The sample in this study were mothers, totaling 30 people. Data were obtained from behavioral questionnaires about dental hygiene before and after being given the book "Healthy Dental Diary". The paired sample t-test statistic test results obtained that the average behavior before was 10.24. After being given the book "Healthy Dental Diary," it became 12.90 with a p-value of 0.000 (p <0.05). The analysis results showed that there were significant changes in behavior regarding dental hygiene before and after being given health education using the book "Healthy Dental Diary". It was concluded that the behavior of mothers in maintaining the cleanliness of their children's teeth and mouth by using the book "Healthy Dental Diary" showed a change in behavior that was better than before. The book "Healthy Dental Diary" is recommended to be used as a media for counseling in changing oral hygiene behavior in the community.